USING THE METHOD OF PEER-TEACHING AT THE LESSONS OF ENGLISH IN MEDICINE - Arzieva D. T. (Journals Park Publishing, 2022)
Peer teaching is not a new concept. It can be traced back to Aristotle's use of "archons", or student leaders, and to the letters of Seneca the Younger. It was firstly organized as a theory by Scotsman Andrew Bell in 1795, and later implemented into French and English schools in the 19th century. Over the past 30-40 years, peer teaching has become increasingly popular in conjunction with mixed ability grouping in K-12 public schools and an interest in more financially efficient methods of teaching .
Keywords: French, history, scools.